Feature Extraction and Elimination using Machine Learning Algorithm for Breast Cancer Biological Datasets - et al., Ajay Kumara (International Journal of Advanced Science and Technology, 2019)
Cancer is a non-curable disease if diagnosed at last stage. It is not easy to diagnose cancer at an early stage. Cancer stage is divided into four stages. First two stages are known as early stage and last two stages as last stage. In order to diagnose at an early stage, Machine Learning is applied. Machine Learning is a field of computer science and Machine Learning algorithm is effective in the operation on biological data. Machine Learning is the technology that can be used to predict the accuracy of cancerous tumor of a human body. Too many features might pose some issues of overfitting the model. In that case, less important features have to be eliminated. Elimination of less important features and including important features create less computational complexity. In this paper, it is marked that with the smaller number of effective features, cancer prediction can be more accurate.